Hsa_circ_0008870 suppresses bone formation of growth plate through inhibition of miR-185-3p/ MAPK1 axis in idiopathic short stature - Wu, Zhiwen; Yuan, Jinghong; Li, Jiantian; Du, Zhi; Yin, Ming; Cheng, Xigao; Liu, Xijuan; Jia, Jingyu (Frontiers in Bioengineering and Biotechnology, 2022)
Idiopathic short stature (ISS) is the most common clinical cause of the short stature with an unclear aetiology and a lack of effective treatment. Circular RNAs have been shown to play a significant regulatory role through various signal transduction pathways in a variety of diseases in recent years. However, the role of circular RNAs on ISS is not yet well-understood and requires a special attention. The differentially expressed circular RNAs were screened by microarray chip analysis, and RT-qPCR was used to verify the expression of hsa_circ_0008870 in ISS patients. Subsequently, in vitro and in vivo experiments were conducted to determine the biological functions of hsa_circ_0008870 in ISS. The authors first confirmed that hsa_ circ_0008870 was downregulated in ISS children. Meanwhile, we also observed that the downregulated hsa_circ _0008870 significantly inhibited chondrocyte proliferation and endochondral ossification in vivo and in vitro. Mechanistically, hsa_circ_0008870 regulates MAPK1 expression by sponge miR-185-3p. This mechanism of action was further verified through rescue experiments. Finally, the authors revealed that the silencing of hsa_circ_0008870 induces low expression of MAPK1 by impairing the sponge action of miR-185-3p, thereby inhibiting chondrocyte proliferation, hypertrophy, and endochondral ossification, which results in a short stature phenotype. In addition to these, we also observed an interesting phenomenon that upregulated of miR-185-3p can in turn inhibit the expression of hsa_circ_0008870 in chondrocytes. This suggests that hsa_circ_0008870 could potentially serve as a therapeutic target for the treatment of ISS.